Perbedaan Status Gizi Baduta Berdasarkan Pola Pemberian Makan Bayi dan Anak Serta Perilaku Hidup Bersih dan Sehat - Apriandana, I Kadek Arya; Nursanyoto, Hertog; Ambartana, I Wayan (Poltekkes Kemenkes Denpasar dan DPD PERSAGI Bali, 2025)
SSGI 2021 results, the prevalence of Wasted in Bali is 2.8% and in Karangasem is 1.9%, Stunted in Bali is 8.0% and in Karangasem is 9.2%, Underweight nutritional status in Bali Province is 6.6% and in Karangasem is 7.3%. WHO and UNICEF recommend four important things in infant and child feeding practices (PMBA). Clean and Healthy Living Behavior (PHBS) is a health activity carried out on self-awareness or awareness of family members so that they can play an active role in public health activities, especially improving nutrition. This study aims to determine the differences between Toddler Nutritional Status; Infant and Child Feeding Patterns; and Clean and Health Living Behavior. This study was an observational study with asample of 57 toddler. This study uses interview methods and anthropometric measurements and analyzed using comparative tests (independent sample t-test). The results showed that there were differences in the nutritional status of toddler based on PMBA patterns (p-value BB/U=0.000, PB/U 0.000, BB/PB=0.002) and there were differences in nutritional status of toddler based on PHBS (p-value BB/U=0.000, PB/U=0.035, BB/PB=0.000). This research can be used as a basis in preparing activity planning and budgets at the Village, Puskesmas and District levels.